Plasmin Proteolysis of Endothelial Cell and Vessel Wall Associated Tissue Factor Pathway Inhibitor - Stalboerger, Paul G.; Panetta, Carmelo J.; Simari, Robert D.; Caplice, Noel M. (Thrombosis and Haemostasis, 2001)
Plasmin is an important protease that mediates clot fibrinolysis and vessel wall extracellular matrix proteolysis. Recently, in vitro studies have suggested that plasmin can cleave and inactivate recombinant TFPI, a major inhibitor of TF-mediated coagulation. We hypothesized that such an interaction may occur in vascular cells expressing TFPI, or in the vessel wall, with implications for thrombolysis. In a series of experiments, we examined the effects of plasmin on cell surface and extracellular matrix (ECM) associated TFPI in endothelial cells (EC) in culture and on EC and smooth muscle cells (SMC) in the vessel wall. Plasmin (0.2 μM) decreased cell surface and matrix associated TFPI activity in cultured endothelial cells by 77 ± 5 % and 69 ± 6% respectively (p < 0.01). Plasminogen, the proenzyme form of plasmin had no such effect on cell surface TFPI or matrix TFPI. Cell surface TFPI antigen measured by fluorescence activated cell sorter (FACS) was also significantly reduced by plasmin. Proteolysis of conditioned medium TFPI was suggested by loss of a ~45kD TFPI on Western Blot analysis following plasmin treatment. Plasmin also proteolysed a ~45kD TFPI protein in the intact ECM of EC, an effect which was inhibited by preincubation with aprotinin, a plasmin inhibitor. Incubation of similar concentrations of plasmin, with homogenates of normal vessel decreased a ~45kD TFPI immunoreactive band on Western blot analysis. Plasmin also decreased surface TFPI activity on frozen sections of normal vessel as measured by an amidolytic assay. Finally, plasmin treatment of atherosclerotic plaque sections caused complete removal of TFPI immunoreactivity associated with luminal EC and intimal SMC, when compared to control treated plaque (n = 3). Together these data suggest that plasmin proteolyses the majority of EC-associated (surface and matrix) TFPI and may remove TFPI from the luminal surface and intima of the vessel wall. TFPI proteolysis in cultured EC was associated with significant reduction in TFPI anticoagulant activity. These data provide evidence that plasmin degradation of TFPI occurs in vascular cells and in the vessel wall and may have implications for rethrombosis following thrombolysis in vivo.
Keywords: Tissue factor; plasmin; endothelium; matrix